The Effect of Synbiotic Consumption on Serum NTproBNP, hsCRP and Blood Pressure in Patients With Chronic Heart Failure: A Randomized, Triple-Blind, Controlled Trial - Shoaei Matin, Shakiba; Shidfar, Farzad; Naderi, Nasim; Amin, Ahmad; Hosseini-Baharanchi, Fatemeh Sadat; Dehnad, Afsaneh (Frontiers in Nutrition, 2022)
Background: In recent years, there has been a positive attitude towards gut microbiota and its effect on cardiovascular diseases, including heart failure. Objective: The purpose of this study was to evaluate the effect of synbiotics on left ventricular hypertrophy by measuring NT-proBNP, and their effect on blood pressure and hsCRP as an inflammatory biomarker in patients with chronic heart failure. Design: In this triple-blind randomized clinical trial, 90 eligible patients were included in the study. They were randomly assigned to receive one capsule (500 mg) of synbiotics or placebo per day for 10 weeks. NTproBNP, hsCRP and blood pressure were measured at the beginning and end of the study. Statistical analysis was performed on 80 patients by using SPSS 24, and p-value <0.05 as statistically significant. Result: At the end of the study, the level of NT-proBNP decreased significantly in the synbiotic group compared to the placebo group (r=-256.55; P= 0.04). However, hsCRP increased in both groups as compared to the beginning of the study, but only in the placebo group the increase in hsCRP was significant (P= 0.01). The results showed that the changes in hs-CRP was not significant between the two groups. No statistically significant differences were observed in systolic and diastolic blood pressure between the two groups at the end of the intervention. Conclusion: Synbiotics have favorable effect on cardiac hypertrophy index (NT-proBNP). Although the inflammatory factor increased in both groups, the significant increase in hsCRP in the placebo group could indicate the beneficial effects of synbiotics on the inflammatory status of these patients.